2011
DOI: 10.1155/2011/579892
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characterization and Antibacterial Activities of Benzyloxybenzaldehydethiosemicarbazone, 3,4‐Dihydroxybenzaldehydeisonicotinoylhydrazone and their Transitional Metal Complexes

Abstract: The synthesis and spectral characterization of benzyloxy-benzaldehydethiosemicarbazone (BBTSC) and the study of antibacterial activity of ligands BBTSC, 3,4-dihydroxybenzaldehydeisoni- cotinoylhydrazone (3,4-DHBINH) and their transition metal complexes was studied. The composition of the metal complexes was also evaluated by using Job’s method, molar-ratio method and Asmus’ method. The antibacterial activities of BBTSC, 3,4-DHBINH and their complexesi.e., Cu(II)-BBTSC, Pd(II)-BBTSC, Cr(VI)- 3,4-DHBINH, Ti(IV)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…It has been shown that the α -(N)-heterocyclic carbaldehyde thiosemicarbazones act as chelating agents of the transition metals and some of them exhibit antitumor activity by inhibiting the biosynthesis of DNA, possibly by blocking the enzyme ribonucleotide diphosphate reductase [ 23 25 ]. On the other hand, the ligand 6-methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone (HmpETSC) and its complexes [Zn(HmpETSC)Cl 2 ] and [Pd(mpETSC)Cl] exhibit antineoplastic activity against colon cancer human cell lines (HCT 116) with IC 50 values of 14.59, 16.96, and 20.65 μ M, respectively [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the α -(N)-heterocyclic carbaldehyde thiosemicarbazones act as chelating agents of the transition metals and some of them exhibit antitumor activity by inhibiting the biosynthesis of DNA, possibly by blocking the enzyme ribonucleotide diphosphate reductase [ 23 25 ]. On the other hand, the ligand 6-methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone (HmpETSC) and its complexes [Zn(HmpETSC)Cl 2 ] and [Pd(mpETSC)Cl] exhibit antineoplastic activity against colon cancer human cell lines (HCT 116) with IC 50 values of 14.59, 16.96, and 20.65 μ M, respectively [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another important band is seen at 3215 cm -1 , corresponding to the stretching of the N-H bond. Taken together, these data confirm the identity of the solid obtained, and these attributions are also in accordance to the literature (Suvarapu et al, 2011).…”
Section: Compound 1a: 34-dihydroxybenzaldehyde Isonicotinoyl Hydrazonesupporting
confidence: 92%
“…The anticancer activity of thiosemicarbazones stems from their chelating ability with transition metal ions by bonding through the sulfur and the azomethinic nitrogen atoms to inhibit the biosynthesis of DNA, possibly by blocking the enzyme ribonucleotide diphosphate reductase. [25,26] Notably, chelating ligands have been used to overcome this high lability, forming thermodynamically stable and kinetically inert cyclopalladated complexes. [27,28] Demertzi et al reported Pd(II) complexes of N 4 -alkyl-2-acetylpyridine thiosemicarbazones inhibits the activity of DNA synthesized in L1210 and P388 cell cultures.…”
Section: Introductionmentioning
confidence: 99%